Joint unloading inhibits articular cartilage degeneration in knee joints of a monosodium iodoacetate-induced rat model of osteoarthritis. Issue 7 (July 2019) - Takahashi, I.; Matsuzaki, T.; Kuroki, H.; Hoso, M.
Summary: Objective: The aim of the study was to examine how mechanical unloading affects articular cartilage degeneration in the patellofemoral (PF) and tibiofemoral (TF) joints of a monosodium iodoacetate (MIA)-induced rat model of osteoarthritis (OA). Design: The study involved 60 male rats. OA was induced by intra-articular injecting MIA into both knee joints. All animals were equally divided into two groups: sedentary (SE) and hindlimb unloading (HU) groups. Histopathological changes in the articular cartilage of the PF and TF joints were evaluated using the Osteoarthritis Research Society International (OARSI) score and modified Mankin score at 2 and 4 weeks after MIA injection. Results: In the SE and HU groups, representative histopathological changes in OA were detected in the PF and TF joints. The OARSI and modified Mankin scores for the PF and TF joints tended to increase over time after the injection of 0.2 mg or 1.0 mg of MIA in the SE and HU groups. Both the scores for the HU group were significantly lower than those for the SE group [OARSI score: P  < 0.0001 (1.0-mg injection at 4 weeks); modified Mankin score: P  = 0.0116 (0.2-mg injection at 4 weeks); P  = 0.0004 and < 0.0001 (1.0-mg injection at 2 and 4 weeks, respectively)]. Conclusion: This study revealed new histological evidence that indicates that unloading condition suppresses articular cartilage degeneration and is beneficial in many areas of basal and clinical research involving OA.